2012
DOI: 10.2147/vhrm.s34874
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow in Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) dementia is a consequence of heterogeneous and complex interactions of age-related neurodegeneration and vascular-associated pathologies. Evidence has accumulated that there is increased atherosclerosis/arteriosclerosis of the intracranial arteries in AD and that this may be additive or synergistic with respect to the generation of hypoxia/ischemia and cognitive dysfunction. The effectiveness of pharmacologic therapies and lifestyle modification in reducing cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(143 citation statements)
references
References 79 publications
9
134
0
Order By: Relevance
“…The link between hypoperfusion and BBB leakage extent and strength complements the previous finding that hypoperfusion is correlated with cognitive decline and hippocampal volume decrease (Roher et al, 2012). Atrophy is one of the hallmarks of AD, but adding atrophy as a confounder did not change the (qualitative) results.…”
supporting
confidence: 75%
“…The link between hypoperfusion and BBB leakage extent and strength complements the previous finding that hypoperfusion is correlated with cognitive decline and hippocampal volume decrease (Roher et al, 2012). Atrophy is one of the hallmarks of AD, but adding atrophy as a confounder did not change the (qualitative) results.…”
supporting
confidence: 75%
“…However, the relationship between reduced CBF and regional atrophy is not clear. In fact, no correlation between the two events was observed by Schuff and colleagues [71], while Roher and colleagues found that AD patients had a 20 % reduction in total CBF that was directly correlated with reduced pulse pressure, hippocampal volume, and cognitive measures, suggesting an association between brain hypoperfusion and dementia [72]. Similarly, a recent study reported significantly lower regional CBF bilaterally in both the frontal and temporal lobes in AD, whereas CBF was lower in left frontal and temporal white matter in vascular dementia patients [73].…”
Section: Impairment Of Cerebral Microcirculation In Alzheimer's Diseasementioning
confidence: 95%
“…While we cannot clearly explain the mechanisms linking metabolic abnormalities with cognitive dysfunctions, there are several hypothesis explaining this issue. Obesity and hypertension are wellestablished risk factors of atherosclerosis and this is one of the risk factors of age-related or neurodegenerative cognitive decline [19]. Antipsychotic-induced obesity is associated with leptin-resistance [20] and previous studies support a role of leptin in cognition [21].…”
Section: Cognitive Performancementioning
confidence: 99%